Can physiological engineering/programming increase multi-generational thermal tolerance to extreme temperature events? - Sorby, K. L.; Green, M. P.; Dempster, T. D.; Jessop, T. S. (The Journal of Experimental Biology, 2018)
Organisms increasingly encounter higher frequencies of extreme weather events as a consequence of global climate change. Currently, few strategies are available to mitigate climate change effects on animals arising from acute extreme high-temperature events. We tested the capacity of physiological engineering to influence the intra- and multi-generational upper thermal tolerance capacity of a model organism, Artemia, subjected to extreme high temperatures. Enhancement of specific physiological regulators during development could affect thermal tolerance or life-history attributes affecting subsequent fitness. Using experimental Artemia populations, we exposed F0 individuals to one of four treatments: heat hardening (28°C to 36°C, 1°C per 10 min), heat hardening plus serotonin (0.056 µg ml-1), heat hardening plus methionine (0.79 mg ml-1) and a control treatment. Regulator concentrations were based on previous literature. Serotonin may promote thermal tolerance, acting upon metabolism and life history. Methionine acts as a methylation agent across generations. For all groups, measurements were collected for three performance traits of individual thermal tolerance (upper sublethal thermal limit, lethal limit and dysregulation range) over two generations. The results showed that no treatment increased the upper thermal limit during acute thermal stress, although serotonin-treated and methionine-treated individuals outperformed controls across multiple thermal performance traits. Additionally, some effects were evident across generations. Together, these results suggest that phenotypic engineering provides complex outcomes, and if implemented with heat hardening can further influence performance in multiple thermal tolerance traits, within and across generations. Potentially, such techniques could be up-scaled to provide resilience and stability in populations susceptible to extreme temperature events.